Endoscopic Retrograde Cholangiopancreatography in Bilioenteric Anastomosis - Eun Taek Park (Korean Society of Gastrointestinal Endoscopy, 2016)
For diagnosis and treatment of pancreatobiliary diseases, endoscopic retrograde cholangiopancreatography (ERCP) is useful method nowadays and its technically success rate is usually in about 90%-95% of patients with normal gastric and pancreaticobiliary anatomy. Recently ERCP is significantly challenging after intestinal reconstruction, particularly in patients who have undergone pancreaticoduodenectomy (PD, classic Whipple's operation) or pylorus-preserving pancreatoduodenectomy (PPPD) with reconstruction. PD and PPPD relate to numerous techniques have been presented for reconstruction of the digestive tract and pancreaticobiliary tree during the resection bilioenteric stricture commonly occurs later in the postoperative course and developed in 5-year cumulative probability of biliary stricture rate of 8.2% and pancreaticoenteric stricture of 4.6%. This complication was no difference in incidence between patients with benign or malignant disease. In PD or PPPD with reconstruction, short pancreatobiliary limb with biliojejunal anastomosis site is made usually, modestly success rate of intubation to blind loop and cannulation with conventional endoscope. However, in combined Reux-en-Y anastomosis, longer pancreatobiliary limb and additional Reux limb are obstacle to success intubation and cannulation by using conventional endoscope. In this situation, new designed enetroscope with dedicated accessories is efficient.